Answer:
6.72 m/s
Step-by-step explanation:
recall that the equations of motion may be expressed as
v² = u² + 2as
where,
v = final velocity,
u = initial velocity = 0 m/s because it is stationary before it starts falling
a = acceleration (in this case because it is falling, it is the acceleration due to gravity = 9.81 m/s²)
s = distance traveled = 2.3m
in our case, if we neglect air resistance, then we simply substitute the known values above into the equation of motion.
v² = u² + 2as
v² = 0² + 2(9.81)(2.3)
v² = 45.126
v = √45.126
v = 6.72 m/s